TP1.2.4The incidence, implications and risk factors for extracolonic findings at CT colonography in a bowel screening population. (28th October 2021) - Di Rollo, Domenic; McMillan, Donald; Horgan, Paul; Mansouri, David
Abstract: Aim: CT virtual colonoscopy (CTC) is increasingly relied upon in bowel screening programmes. Concern remains regarding the prevalence of incidental extra-colonic findings (ECF). The present study reports on the prevalence and implications of ECF as part of a UK bowel screening programme. Methods: Reports for 400 consecutive CTCs carried out as part of the Scottish Bowel Screening Programme were examined. Intra and extracolonic findings were recorded using the CT Colonography Reporting and Data System (C-RADS). Medical records pertaining to ECF follow-up were examined. Cost analysis was performed. Results: 394 patients were included. 146 (37%) were males. Median age was 65 years, median follow-up was 72 months (Range 32-110). 92 (23%) patients had CTC as their primary investigation, 302 (77%) patients underwent CTC due to failed colonoscopy. Overall, 244/394 (62%) patients had ECF with only 45/394 (11%) found to have colonic pathology. 65/394 (16%) had moderately or highly significant ECF, (C-RADS E3-4 ). Of the 244 patients with ECF, 59 (24%) underwent further investigation, estimated cost £17, 589. The majority, 37/59 (63%) were found to have benign disease after follow-up. Conclusion: ECF at CTC are more frequent than colonic findings. The majority of ECF investigated are found to be benign yet a quarter of ECF are further investigated at a cost to the health service and the patient. Clinicians should be judicial when ordering and consenting patients with regards ECF and its implications if CTC is considered. Particularly when the test is part of a public funded and voluntary screening programme.